Macro- and Micropropagation of Moringa oleifera Lam (Moringaceae): A Mini Review (Asian Journal of Plant Biology, 2022)
The most popular member of the family Moringaceae is Moringa oleifera Lam. While originally from the western sub-Himalayas, India, Pakistan, Asia, and Africa, this plant has since found its way around the world. Growth of the plant is slow in areas with harsh climates, despite evidence of its excellent adaptability in tropical regions. Moringa oleifera has been studied for its potential as a biodiesel source, as well as its usage as a natural coagulant for water purification. The maturation period of Moringa oleifera is rather long because it is frequently cultivated from seeds. Therefore, it is currently unable to meet the growing demand for this species to fulfil its many household, nutritional, economic, and medical purposes. This review covers the uses and the establishment, maintenance, and development of mass propagation of the plant. The review also covers extensive parts of the plant, from a single cell to an entire plant, under artificial and axenic conditions is the focus of plant tissue culture (PTC), which is an integral part of Plant Biotechnology due to the many benefits it offers over traditional methods of propagation. Plant hormones have been shown to improve the success of vegetative propagation from cuttings, but in order to obtain uniform planting materials, tissue culture techniques involving plant materials like nodal segments, indirect organogenesis, multiplication using immature seeds, and regeneration of axillary cotyledons and buds are preferable.
Keywords: Moringa oleifera; Vegetative propagation; Traditional medicine; Plant tissue culture; Plant hormones